A pilot study of EUS-guided fiducial insertion for the multidisciplinary management of gastric cancer - Chandran, Sujievvan; Vaughan, Rhys; Efthymiou, Marios; Sia, Joseph; Hamilton, Christopher (Endoscopy International Open, 2014)
Background and study aims: The 5-year survival rates for gastric cancer remain poor despite evolving therapies, and fiducial insertion via endoscopic ultrasound (EUS) is novel within this setting. We aimed to assess the feasibility of fiducial insertion for response assessment and anatomic localization in patients with gastric cancer.Patients and methods: A prospective phase II feasibility study was undertaken at Austin Health (Victoria, Australia) from February 2011 to November 2012. Consecutive adult patients were enrolled who had primary adenocarcinoma of the stomach with American Joint Committee on Cancer stage T1 – 3,N0 – 1,M0 – 1a and Eastern Cooperative Oncology Group (ECOG) performance status 0 or 1. In addition, the patients were medically suitable for gastrectomy and chemotherapy/chemoradiotherapy. Gold fiducial markers were inserted under EUS guidance into the margins of the gastric cancer primary. The main outcome was successful insertion of the fiducial without complications for response assessment and anatomic localization. Results: A total of 15 fiducials were successfully inserted into 7 (88 %) of 8 patients. No immediate or delayed complications were noted. One patient proceeded to image-guided radiotherapy through the use of fiducials and is disease free at 12 months. Fiducials were used to assess treatment response in all patients who underwent computed tomographic imaging after insertion. Follow-up computed tomography with fiducial placement improved anatomic localization and estimation of the gastric cancer primary size in 3 (60 %) of 5 patients.Conclusions: Within the limitations of our small study cohort, fiducials were placed in gastric cancers under EUS guidance without complications, and placement was successful in the majority of our patients. Although potential benefits exist, there remain substantial limitations to the generalization of this technique across our patient population.